Effect of biofertilizer (Em1) and seaweed extract (Alga 600) on growth and productivity of strawberry Fragaria × ananassa plant - Alomar, Mohamad; Bayerli, Roula; Sharaby, Hanan (Iraqi Journal of Science, 2023)
This experiment was carried out in the greenhouse of Al-Adawi area of the Damascus Governorate, and labs of the Horticulture Department, Faculty of Agriculture, Damascus University during the period 2020-2021, to study the effect of biofertilizer, Em1 (0, 4, 8 ml/l), and seaweed extract, Alga 600 (0, 1, 2 g/l) and their interactions on growth and productivity of strawberry plant cv. Festival. data were calculated after six months of culture. The combination treatment of Em1, (8 ml/l) and Alga 600 (2 g/l) resulted in the best morphological parameters (23,93 cm, 27.87, 138.81 cm² for plant height, leaf number, and area respectively), physiological parameters (10.30 %, 60.00 mg/100 gm wet weight, 0.59 % for total soluble solids, vitamin C and titratable acidity respectively), and productivity parameters (20.07, 16.4, 250.72 g/ plant for flowers and fruits number/plant and plant yield respectively). The lowest values, however, were obtained in control non-treated plants.